1997
DOI: 10.1080/00222899709600828
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Kinematic Characteristics in the Motion of Lifted Weight

Abstract: It has been widely shown that human observers are able to perceive lifted weight from the observation of a point-light display of the lifter's action. In the experiments reported here, the kinematic information used by observers to perceive a lifted weight was determined. In Experiment 1, observers (N = 30) were able to identify weights (5, 10, 15, 20, and 25 kg) successfully by observing only the lift phase of the action. Other procedures, such as walking while holding the weight and placing the weight on a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 25 publications
6
48
0
Order By: Relevance
“…Moreover, when transcranial magnetic stimulation (TMS) is applied during the mere observation of actions, the primary motor cortex (M1) becomes increasingly activated in a strictly time-locked and gle these distinct visual features and to characterize their relative contribution in mediating force-encoding within the observer's motor system. Overall, three types of visual features can be distinguished that may contribute to a person's ability to infer the applied force from observing the grasping and lifting of a bottle: A first important cue is the perceived kinematic pattern by which the bottle is grasped and lifted (Bingham, 1987;Grezes, Frith, & Passingham, 2004;Hamilton, Joyce, Flanagan, Frith, & Wolpert, 2007a;Shim & Carlton, 1997). For example, if the bottle is heavy, the durations of the grasp-and lift-phase will be longer, than for lifting a lighter bottle.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when transcranial magnetic stimulation (TMS) is applied during the mere observation of actions, the primary motor cortex (M1) becomes increasingly activated in a strictly time-locked and gle these distinct visual features and to characterize their relative contribution in mediating force-encoding within the observer's motor system. Overall, three types of visual features can be distinguished that may contribute to a person's ability to infer the applied force from observing the grasping and lifting of a bottle: A first important cue is the perceived kinematic pattern by which the bottle is grasped and lifted (Bingham, 1987;Grezes, Frith, & Passingham, 2004;Hamilton, Joyce, Flanagan, Frith, & Wolpert, 2007a;Shim & Carlton, 1997). For example, if the bottle is heavy, the durations of the grasp-and lift-phase will be longer, than for lifting a lighter bottle.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PLD research has identified that sufficient information is contained in movement kinematics for observers to discriminate the weights of objects lifted by an actor (Runeson & Frykholm, 1981), even when the actor feigns the weight of the object that is being lifting (Runeson & Frykholm, 1983). Specifically, the actor's hip angle, the period of time between the actor establishing a purchase and lifting the object, and lifting velocity contribute to the observer's ability to detect the true weight of a lifted object (Bingham, 1987;Hamilton & Grafton, 2007;Shim & Carlton, 1997). However, the extrinsic visual characteristics of a lifted object also represent sources of information that can influence the perception of the lifting movement (see R. S. Johansson & Cole, 1994, for a review).…”
mentioning
confidence: 99%
“…Specifically, the experts pick up of proximally (earlier) occurring advance information suggests their advantage lies in their ability to perceive and understand kinematic information -a contention supported through studies of "Point Light Displays" (PLDs) presenting only kinematic information (Abernethy & Zawi, 2007;Kozlowski & Cutting, 1977;Shim & Carlton, 1997). Further, to their ability to utilize advance information, it appears skilled performers adopt a more 'global' rather than 'local' strategy, relying on multiple sources of information to inform their judgments (Williams, Huys, Ca帽al-Bruland, & Hagemann, 2009).…”
Section: Perceptual Expertisementioning
confidence: 99%